Murder Learning Model Assisted by Metacognitive Scaffolding to Improve Students’ Scientific Literacy and Numeracy Skills through Science Studies in Elementary Schools - Tegeh, I. M.; Astawan, I. G.; Sudiana, I. K.; Kristiantari, M. G. R. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
Teachers have not systematically handled science learning. Due to teachers’ lack of creativity in creating science learning that provides learning experiences, students cannot develop literacy and numeracy. Preliminary research studies found low learning outcomes in science studies with significant literacy and numeracy skills weaknesses. This study aims to analyze the effect of the Murder learning model assisted by Metacognitive Scaffolding on students' scientific literacy and numeracy skills through science studies in elementary schools. With a non-equivalent posttest-only control group design, this research is a quasi-experimental study. The population in this study was 173 people, while 60 people divided into two classes were chosen by random sampling. Data on scientific literacy and numeracy skills were collected using a test instrument which consisted of 35 questions. The instrument was gone through a validation process to measure its validity and reliability. A MANOVA test with the IBM SPSS Statistics 21.0 program was utilized to analyze the data. The hypothesis test obtained a significance value of 0.000 (Sig 0.05). The average score of scientific literacy skills was 77.67, and 75.37 for numeracy skills. Based on this, it can be concluded that there is a significant effect of the Murder learning model assisted by Metacognitive Scaffolding on students' scientific literacy and numeracy skills through science studies in elementary schools.